Reconstruction of the auricular rupture: A case report of treatment of ear trauma - Daniswara, Deoni; Widuri, Asti; Fakhriani , Rizka (Institute of Computer Science (IOCS), 2025)
Auricular rupture is one of the most common ear defects caused by trauma on facial and head regions. Traffic accidents, accidents at home, fights, and human bites are common causes of ear injuries based on several epidemiological studies. In this study, we report a case of ear trauma auricular rupture, with appropriate treatment and the things to watch out for during treatment. A 19-year-old man came to the Emergency Department due to a traffic accident. The results of the vital signs examination were within normal limits, found an injury to the left auris; the wound penetrated the left auris from the Helix to the antihelix with a wound length of approximately 4 cm. Bleeding was controlled with a compression splint using gauze and ligature. The patient underwent elective surgery, which was successful and without complications. Ear trauma involves cartilage is a challenge to treat reconstruction for surgeons. The main treatment for auricular rupture is closure of the open cartilage, skin and prevent complications.